QTc Interval Prolongation in Drug Resistant-Tuberculosis Patients Treated with Shorter Treatment Regimen (Medico Legal Update, 2021)
Background: Shorter Treatment Regimen (STR) is a combination of treatments with a shortened periodfrom 20-24 months to 9-11 months. Shortened treatment requires a higher dose of drug to kill resistantbacteria. Corrected QT (QTc) interval prolongation is one of the severe side effects of treatment.Objective: This study aimed to find the factors of QTc prolongation in Drug Resistant-Tuberculosis (DRTB) patients treated with STR during an intensive phase.Method: An analytical retrospective study was conducted at Dr. Soetomo General Academic Hospital,Surabaya, Indonesia. DR-TB patients on the STR regimen were collected based on medical records betweenSeptember 2017 to August 2018. QTc interval was calculated by Fredericia formula. The relationshipbetween QTc interval at baseline and occurrence of QTc prolongation was analyzed using Chi-Square offisher’s exact test.Results: Among 108 patients on the STR regimen, there were 20 (28%) patients experienced moderateQTc prolongation (471-500 ms), and 31 (28%) patients had severe QTc prolongation (>500 ms) during fourmonths observation period in STR treatment. The prolonged QTc interval was significantly related to QTcinterval at baseline (p = 0.001). The QTc interval at baseline correlated significantly with the start time ofQTc prolongation (p < 0.001). Risk factors of age, gender, comorbid, hypertension, and potassium level atbaseline had a significant negative correlation to QTc prolongation.Conclusion: The prolonged QTc interval was significantly related to QTc interval at baseline. The QTcinterval at baseline correlates significantly with the start time of QTc prolongation.